2009
DOI: 10.1108/17538350910993430
|View full text |Cite
|
Sign up to set email alerts
|

Are healthy and successful organizations working accordingly to quality management?

Abstract: Purpose -The purpose of this paper is to examine whether healthy and successful organizations are working accordingly to Quality Management. The purpose is also to describe in more detail how they are working. Design/methodology/approach -Three Swedish organizations that have shown excellence in leadership, internal partnership, working environment and profitability have been examined, to find out what methodologies they have used for their success. To discover whether these healthy and successful organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
0
21
0
1
Order By: Relevance
“…Furthermore, Lindberg (2006), underlines that there would be substantial advantages for individuals, workplaces and society if the number of coworkers affected by physical and mental illnesses could be reduced. In addition, Bäckström, Larsson and Wiklund (2009) state that organizations that were working according to Quality Management had healthy co-workers and low levels of sickness absence.…”
Section: Health-related Quality Management and Its Underlying Dimensionsmentioning
confidence: 99%
“…Furthermore, Lindberg (2006), underlines that there would be substantial advantages for individuals, workplaces and society if the number of coworkers affected by physical and mental illnesses could be reduced. In addition, Bäckström, Larsson and Wiklund (2009) state that organizations that were working according to Quality Management had healthy co-workers and low levels of sickness absence.…”
Section: Health-related Quality Management and Its Underlying Dimensionsmentioning
confidence: 99%
“…One of these studies combines interviews with workshops (Bäckström et al 2009), one study combines interviews with questionnaires (Krok & Eklund 2010), one study combines interviews with questionnaires and video analysis (Lindqvist 2007), one study combines interviews with observations (Wallo et al 2012), and finally one study combines interviews with a review of documents.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, one study describes a waste disposal service company (Krok & Eklund 2010) and one study describes the National Road Safety Office (Grundén 2009). In addition, two studies describe both public sector medical care organisations and private companies (Bäckström et al 2009;Larsson & Vinberg 2010. Two of the nine research studies, conducted in private companies, describe private banks (Wreder 2007;Wreder et al 2007) Arnetz (2005) explored which aspects of leadership are important in order to cope with changes and stress factors, during the process of change, when medical care organisations are set to improve their company performance and effectivity. The author concluded that the management's ability to communicate and focus on organisational objectives can improve the overall wellbeing of their employees.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations